Pengaruh pendapatan asli daerah, dana alokasi umum, dan dana alokasi khusus terhadap pertumbuhan ekonomi Kabupaten/Kota Provinsi Jambi - Anjelina, Pebby; Zamzami, Zamzami; Nurhayani, Nurhayani (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2019)
This study aims, (1) To analyze the development of local revenue, general allocation funds, special allocation funds, and economic growth in the districts/municipalities of Jambi Province (2) To determine the effect of local revenue, general allocation funds, and special allocation funds on district economic growth/City of Jambi Province partially and simultaneously. Data sourced from the Jambi Province Central Bureau of Statistics and the Directorate General of Fiscal Balance using panel data analysis methods and using descriptive analysis tools. Based on the results of data processing, the following results are obtained: First, the average development of the variable local revenue, general allocation funds, special allocation funds, and fluctuating economic growth from year to year. second, (1) local revenue and special allocation funds have a negative and significant effect on the economic growth of districts/cities in Jambi Province. (2) General allocation funds have a negative and insignificant effect on the economic growth of districts/cities in Jambi Province. Keywords: Economic growth, Locally-generated revenue, General allocation funds, Special allocation funds Province.